2013
DOI: 10.3855/jidc.2938
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of ESBL genes in Escherichia coli and Klebsiella pneumoniae causing nosocomial infections in Vietnam

Abstract: Background: Extended-spectrum β-lactamases (ESBLs) are enzymes capable of hydrolyzing oxyimino-β-lactams and inducing resistance to third generation cephalosporins. The genes encoding ESBLs are widespread and generally located on highly transmissible resistance plasmids. We aimed to investigate the complement of ESBL genes in E. coli and Klebsiella pneumoniae causing nosocomial infections in hospitals in Ho Chi Minh City, Vietnam. Methodology: Thirty-two non-duplicate isolates of E. coli and Klebsiella pneumon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…Specifically, we found that, in comparison to XDR strains, non-XDR organisms exhibited a low rate of resistance against aminoglycosides but a high degree of resistance against third-and fourthgeneration cephalosporins. The resistance rates associated with the antimicrobials profiled in this study support previous data from Vietnamese hospitals, which have shown a substantial increase in the rate of isolation of MDR Gramnegative organisms [26].…”
Section: Discussionsupporting
confidence: 88%
“…Specifically, we found that, in comparison to XDR strains, non-XDR organisms exhibited a low rate of resistance against aminoglycosides but a high degree of resistance against third-and fourthgeneration cephalosporins. The resistance rates associated with the antimicrobials profiled in this study support previous data from Vietnamese hospitals, which have shown a substantial increase in the rate of isolation of MDR Gramnegative organisms [26].…”
Section: Discussionsupporting
confidence: 88%
“…This plasmid‐mediated ampC ‐like gene was previously found to spread among E. coli and Salmonella in food animals, retail meat and humans . The different type and frequency of ESBL genes present is likely as a result of different geographical areas, different types of cephalosporins used, and different antimicrobial selective pressure . The latter is supported by the observation that all the ESBL producers were multi‐resistant, suggesting the possible co‐selection of resistance genes.…”
Section: Discussionmentioning
confidence: 75%
“…Antimicrobial resistance (AMR) is a serious threat to public health and patient safety in Europe, leading to mounting healthcare costs, patient treatment failure, and deaths [15]. Several classes of bacteria have already exhibited multidrug resistance to antibiotics, such as Klebsiella pneumoniae and E. coli strains producing extended-spectrum beta-lactamase (ESBL), which hydrolyses the beta-lactam ring of penicillin, cephalosporins, and other related antibiotics, contributing to treatment failure [16][17][18].…”
Section: Resultsmentioning
confidence: 99%